Working memory capacity and text comprehension performance in children with dyslexia and dyscalculia: a pilot study - López-Resa, Patricia; Moraleda-Sepúlveda, Esther (Frontiers in Psychology, 2023)
Different research over the years has shown how the executive processes of Working Memory are a fundamental area that allows the performance of complex cognitive tasks such as language comprehension, reading, mathematical skills, learning or reasoning. Therefore, scientific evidence shows that they are altered in people with dyslexia and dyscalculia. The aim of this research was to study the relationship between semantic updating ability and reading comprehension depending on whether or not the information content had a mathematical character between the two disorders. A Pilot Case Study was carried out for this purpose. The sample consisted of 40 participants aged 6 to 11 years, 20 of them with a diagnosis of dyslexia and the remaining 20 with a diagnosis of dyscalculia. The results indicate that people with dyslexia show more difficulties in all those tasks that require reading. People with dyscalculia obtain worse results in the tasks of stimulus integration and reading comprehension of texts with mathematical content. Furthermore, the correlation between the different areas evaluated shows that people with dyslexia and dyscalculia develop different cognitive processes. Therefore, it is necessary to continue insisting on the importance of explicit work on working memory, since it is a determining and fundamental area in the development of written language comprehension. Con formato: Español (España) Con formato: Español (España) Con formato: Español (España) Con formato: Español (España)